Do Painted Nails Increase Bacterial Transmission in Healthcare Environments? A Literature Review - Brudniak, Katarzyna; Garbino, Karolina; Czyczerska , Magdalena; Szuścik, Antoni; Gadżała, Katarzyna; Przygodzka, Sabina; Mach, Maciej; Rutkiewicz, Maciej (Quality in Sport, 2025)
Introduction: Healthcare-associated infections (HAIs) continue to be a significant global concern, leading to increased patient morbidity, prolonged hospitalizations, and elevated healthcare costs. Hand hygiene remains the most critical part of infection prevention, however the use of nail polish and artificial nails has raised questions regarding their possible contribution to bacterial transmission. Aim of study :The aim of this study is to collect and examine whether painted nails significantly influence bacterial spread in healthcare settings, focusing on nail surface properties, hand hygiene practices and existing guidelines. Materials and Methods: A literature review was conducted with PubMed and other medical databases using appropriate keywords. Data from clinical trials and reviews were analyzed. Conclusions: Intact nail polish does not pose a significant risk for bacterial transmission in healthcare environments when proper hand hygiene protocols are followed. Emphasis should remain on keeping short, clean nails and adhering to strict hand hygiene practices to reduce healthcare-associated infections (HAIs). Keywords: nail polish, hand hygiene, healthcare-associated infections, articial fingernails in a hospital environment